Kreasi Olahan Kripik Daun Kelor - marwana, marwana; Rukhayati (Sambulu Gana : Jurnal Pengabdian Masyarakat, 2024)
Moringa leaves can be processed into chips which have added value and are economical. However, consumption of Moringa leaves is low due to poor processing technology, low economic value, and the image as poor people's food. This service activity aims to increase the added value of Moringa leaf products by processing them into long-lasting chips. The methods used are drying, mixing spices, and packaging. The results showed that Moringa leaf chips had a crunchy texture, savory taste and fragrant aroma. Moringa leaf chips can also be stored for months without reducing their quality. Thus, Moringa leaf chips can be an alternative staple food and a source of income for housewives, as well as an effort to strengthen local products.